Study of TiO2-SiO2 nanofluids for heat transfer enhancement in solar collector system - Mohd Amiruddin Fikri Yaakob (2023)
Nowadays, the energy consumption of water heating system is high, and it depends on the use of gas and electricity. The demand for electricity and gas is getting higher and, at the same time, increasing the living cost. Therefore, renewable energy, such as solar energy, is one technique for the government to overcome the worrying energy crisis. The objective of the present study is to investigate the thermo-physical properties, thermal performance and optimize the variables involved in the absorber solar collector simulator using the Response Surface Method of TiO2-SiO2 nanofluids based water-ethylene glycol mixture. Initially, a two-step method was applied to prepare TiO2-SiO2 nanofluids for volume concentrations 0.3, 0.5, 0.7 and 1.0% with two ratios of 30:70 and 70:30 mixture with a ratio of 60:40 for water-ethylene glycol, respectively. Each nanofluid with variable volume concentrations was exposed to the intensity of light under a solar simulator with 300, 500, 700 and 900 W/m2 for 30 minutes, of which 15 minutes was the heating period and the next 15 minutes was for cooling. Then, the optimization of the output temperature was done with the help of statistical tool software employing ANOVA analysis to determine the significant factors and establish the relation between the factors. The desirability approach was used in determining the optimal conditions of factors and their responses under the Box Behnken design. The characteristics with a ratio of 30:70 is much better compared to a ratio of 70:30. For thermal conductivity of TiO2-SiO2 nanofluids with a ratio of 30:70 increased with the increase of particle concentration and temperature. Meanwhile, the dynamic viscosity ratio of 30:70 increased with the increase in particle concentration and decreased with the nanofluid temperature. Then, the best parameter for the useful energy, heat loss and efficiency of the experiment was at 135° for the angle of sunlight, 5L/min for flow rate and 900 W/m? for the Intensity of light. The outcome of the Response Surface Method for optimization indicated that the optimum value for the absorber solar collector with 0.3% for the ratio of 30:70 was the best volume concentration and the same with the angle of sunlight, the intensity of light and flow rate, which is 51°, 339 W/m' and 4 L/min respectively. Therefore, this finding justifies that the optimization of the absorber solar collector via the Box-Behnken design technique could facilitate the working fluid, such as TiO2-SiO2 nanofluids, in achieving higher output temperature. The output temperature of TiO2-SiO2 nanofluids as working fluid for absorber solar collector is at 50.02 °C. Nevertheless, an experiment applying the solar water heating system to authentic places such as a hospital and clinic as a pilot plant to reduce the monthly cost of the company based on actual data used of hot water is recommended for future work which is not included in the scope of the present study.